Establishing a Regional Trauma Preventable/Potentially Preventable Death Rate. Issue 2 (February 2020) - Drake, Stacy A.; Holcomb, John B.; Yang, Yijiong; Thetford, Caitlin; Myers, Lauren; Brock, Morgan; Wolf, Dwayne A.; Cron, Stanley; Persse, David; McCarthy, James; Kao, Lillian; Todd, S. Rob; et al.
Abstract : Objective: To establish a trauma preventable/potentially preventable death rate (PPPDR) within a heavily populated county in Texas. Summary: The National Academies of Sciences estimated the trauma preventable death rate in the United States to be 20%, issued a call for zero preventable deaths, while acknowledging that an accurate preventable death rate was lacking. In this absence, effective strategies to improve quality of care across trauma systems will remain difficult. Methods: A retrospective review of death-related records that occurred during 2014 in Harris County, TX, a diverse population of 4.4 million. Patient demographics, mechanism of injury, cause, timing, and location of deaths were assessed. Deaths were categorized using uniform criteria and recorded as preventable, potentially preventable or nonpreventable. Results: Of 1848 deaths, 85% had an autopsy and 99.7% were assigned a level of preventability, resulting in a trauma PPPDR of 36.2%. Sex, age, and race/ethnicity varied across preventability categories ( P < 0.01). Of 847 prehospital deaths, 758 (89.5%) were nonpreventable. Among 89 prehospital preventable/potentially preventable (P/PP) deaths, hemorrhage accounted for 55.1%. Of the 657 initial acute care setting deaths, 292 (44.4%) were P/PP; of these, hemorrhage, sepsis, and traumatic brain injury accounted for 73.3%. Of 339 deaths occurring after initial hospitalization, 287 (84.7%) were P/PP, of these 117 resulted from sepsis and 31 from pulmonary thromboembolism, accounted for 51.6%. Conclusions: The trauma PPPDR was almost double that estimated by the National Academies of Sciences. Data regarding P/PP deaths offers opportunity to target research, prevention, intervention, and treatment corresponding to all phases of the trauma system.